RANCANGAN ALAT PENDETEKSI KETERSEDIAAN FLIGHT PROGRESS STRIP BERBASIS Internet Of Things (IoT) DI UNIT FDPS/RDPS JAKARTA AIR TRAFFIC SERVICE CENTER (JATSC) - feti fatonah; suse lamtiar; Aliefiah Oktaviana; Rachmat Ali (Jurnal Penelitian)
In JATSC Radar Data Processing System and Flight Data Processing System (RDPS / FDPS) Unit has one of the systems, namely Enhance- Jakarta Automation Air Traffic Service (E-JAATS). This equipment plays an important role in aviation services. The Working Processing (CWP) controller has equipment, one of which is to produce a flight progress strip. Flight strip is equipment used by ATC to keep a record of instructions issued and then used as a representation of all flights in a particular sector. RDPS / FDPS unit technicians are tasked with ensuring the availability of the flight strip. One of the problems that occurred when doing On The Job Training at the Jakarta Air Traffic Service was that RDPS / FDPS technicians did not know the availability of the flight strip every time and waited for information from ATC when the flight strip ran out. Based on this situation, the authors want to design a flight strip availability detection tool using NodeMCU and an infrared sponsor that can be accessed via Blynk APP so that it can help technicians find out information on flight strip availability at any time and immediately make changes when the flight strip will run out.